Incidence, hospital costs and in-hospital mortality rates of surgically treated patients with traumatic cranial epidural hematoma - Ibrahim Burak Atci; Hakan Yilmaz; Mehmet Yaman; Oguz Baran; Okan Türk; Bilgehan Solmaz; Ümit Kocaman; Nuriye Guzin Ozdemir; Nail Demirel; Ayh an Kocak (Romanian Neurosurgery, 2018)
Background: In this study, the patients who were operated in two clinics due to traumatic cranial epidural hematoma (EDH) were assessed retrospectively and the factors that increase the costs were tried to be revealed through conducting cost analyses. Methods: The patients who were operated between 2010 and 2016 with the diagnosis of EDH were assessed in terms of age, sex, trauma etiology, Glasgow coma scale (GCS) at admission, the period from trauma to hospital arrival, trauma-related injury in other organs, the localization of hematoma, the size of hematoma, length of stay in the intensive care unit (ICU), length of antibiotherapy administration, number of consultations conducted, total cost of in-hospital treatments of the patients and prognosis. Results: Distribution of GCS were, between 13-15 in 18 (36%) patients, 9-13 in 23 (46%) patients and 3-8 in 9 (18%) patients. The reasons for emergency department admissions were fall from high in 29 (58%) patients, assault in 11 (22%) patients and motor vehicle accident in 10 (20%) patients. The average cost per ICU stay was 2838 $ (range=343-20571 $). The average cost per surgical treatment was 314 $. ICU care was approximately 9 times more expensive than surgical treatment costs. The mortality rate of the study cohort was 14% (7 patients). Conclusion: The prolonged period of stay in the ICU, antibiotherapy and repeat head CTs increase the costs for patients who are surgically treated for EDH.